Prognostic impact of metastatic lymph node ratio on gastric cancer after curative distal gastrectomy - Huang, Chang-Ming (The WJG Press and Baishideng, 2010)
AIM: To investigate the prognostic impact of metastatic lymph node ratio (rN) on gastric cancer after curative distal gastrectomy. METHODS: A total of 634 gastric cancer patients who underwent curative resection (R0) of lymph nodes at distal gastrectomy in 1995-2004. Correlations between positive nodes and retrieved nodes, between rN and retrieved nodes, and between rN and negative lymph node (LN) count were analyzed respectively. Prognostic factors were identified by univariate and multivariate analyses. Staging accuracy of the pN category (5th UICC/TNM system) and the rN category was compared according to the survival rates of patients. A linear regression model was used to identify the relation between rN and 5-year survival rate of the patients. RESULTS: The number of dissected LNs was related with metastatic LNs but not related with rN. Cox regression analysis showed that depth of invasion, pN and rN category were the independent predictors of survival (P < 0.05). There was a significant difference in survival between LN stages classified by the rN category or by the pN category (P < 0.05). However, no significant difference was found in survival rate between LN stages classified by the pN category or by the rN category (P > 0.05). Linear regression model showed a significant linear correlation between rN and the 5-year survival rate of gastric cancer patients (β = 0.862, P < 0.001). Pearson’s correlation test revealed that negative LN count was negatively correlated with rN (P < 0.001). CONCLUSION: rN category is a better prognostic tool than the 5th UICC pN category for gastric cancer patients after curative distal gastrectomy. Increased negative LN count can reduce rN and improve the survival rate of gastric cancer patients.